The antipsychotic drug lurasidone inhibits coronaviruses by affecting multiple targets - Sara Baroni; Tea Carletti; Manuela Donalisio; Irene Arduino; Irene Cazzaniga; Irene Cazzaniga; Toni Giorgino; Francesca Esposito; Alessia Porta; Luisa Diomede; Ada De Luigi; Marco Gobbi; et al. (Frontiers in Cellular and Infection Microbiology)
Coronaviruses (CoVs) share key genomic elements critical for viral replication, suggesting the feasibility of developing therapeutics with efficacy across different viruses. In a previous work, we demonstrated the antiviral activity of the antipsychotic drug lurasidone against both SARS-CoV-2 and HCoV-OC43. In this study, our investigations on the mechanism of action of lurasidone suggested that the drug exhibits antiviral activity by targeting the papain-like protease (PL-Pro) of both viruses, and the Spike protein of SARS-CoV-2, thereby hampering both the entry and the viral replication. In vitro assays demonstrate that lurasidone significantly reduces viral load in infected cells, showing that the drug is a promising candidate for further development as a dual-action antiviral, offering a potential new strategy in the fight against COVID-19 and other coronavirus-related diseases.